KERAPATAN DAN VIABILITAS SPORA BEAUVERIA BASSIANA (BALS.) AKIBAT SUBKULTUR DAN PENGAYAAN MEDIA, SERTA VIRULENSINYA TERHADAP LARVA PLUTELLA XYLOSTELLA (LINN.) - Siti Herlinda, Muhamad Darma Utama, Yulia Pujiastuti, dan Suwandi . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2006)
Density and  viability of spores  of  Beauveria bassiana (Bals.) Vuill. due to sub-cultures and media enriched, and  its virulence against larvae of Plutella xylostella (Linn.) This laboratory research was conducted to determine density and  viability of spores of Beauveria bassiana due to sub-cultures and media enriched, and to investigate the fungi virulence againts larvae of Plutella xylostella. B. bassiana was grown in Saborroud Dextrose Broth (SDB)  cultures enriched  with  cricket powder. The results showed  that the best sub-culture was the fourth sub-culture enriched with cricket powder, producing  6.05 x 108 spores/ml with 30.7% viability.  The highest  larval mortality was found in the second sub-culture enriched with cricket powder which was reach  78.33%.  The spore density and viability, and  virulence of B. bassiana  grown in sub-culture  without  cricket powder enrichment was consistently decreasing  from the second sub-culture to the eighth. Sub-cultures enriched with cricket powder  could increase density, viability, and virulence of  B. bassiana  in  every sub-culture. Overall, the  enrichment with  cricket powder  up to 0.5% could  increase the density, viability, and virulence of B. bassiana.